FGF19 Promotes the Proliferation and Insulin Secretion from Human Pancreatic β Cells Via the IRS1/GLUT4 Pathway - Zeng, Ting; Tang, Xi; Bai, Xiaosu; Xiong, Haiyan (Experimental and Clinical Endocrinology & Diabetes, 2024)
Background Type 2 diabetes mellitus (T2DM) is a commonly observed complication associated with obesity. The effect of fibroblast growth factor 19 (FGF19), a promising therapeutic agent for metabolic disorders, on pancreatic β cells in obesity-associated T2DM remains poorly understood.Methods Human pancreatic β cells were cultured with high glucose (HG) and palmitic acid (PA), followed by treatment with FGF19. The cell proliferation, apoptosis, and insulin secretion were evaluated by CCK-8, qRT-PCR, ELISA, flow cytometry, and western blotting. The expression of the insulin receptor substrate (IRS)/glucose transporter (GLUT) pathway was evaluated. The interaction between FGF19 and IRS1 was predicted using the STRING database and verified by co-immunoprecipitation and immunofluorescence. The regulatory effects of the IRS1/GLUT4 pathway on human pancreatic β cells were assessed by overexpressing IRS1 and silencing IRS1 and GLUT4.Results HG+PA treatment reduced the human pancreatic β cell proliferation and insulin secretion and promoted cell apoptosis. However, FGF19 treatment restored these alterations and significantly increased the expressions of IRS1, GLUT1, and GLUT4 in the IRS/GLUT pathway. Furthermore, FGF19 and IRS1 were found to interact. IRS1 overexpression partially promoted the proliferation of pancreatic β cells and insulin secretion through GLUT4. Additionally, the silencing of IRS1 or GLUT4 attenuated the therapeutic effects of FGF19.Conclusion In conclusion, FGF19 partly promoted the proliferation and insulin secretion of human pancreatic β cells and inhibited apoptosis by upregulating the IRS1/GLUT4 pathway. These findings establish a theoretical framework for the clinical utilization of FGF19 in the treatment of obesity-associated T2DM.
Keywords: fibroblast growth factor 19; type 2 diabetes mellitus; IRS1/GLUT4 pathway; human pancreatic β cells; insulin secretion